Changes over treatment in total clinical symptom scores in patients with traumatic keratitis - V.M. Sakovych; T.O. Ostrikova (Journal of Ophthalmology, 2018)
Background: Since corneal tissue hypoxia develops in patients with traumatic keratitis, investigation of changes over treatment in clinical symptom scores in patients with traumatic keratitis undergoing adjunctive hyperbaric oxygenation (HBO) is of practical value.